2021
DOI: 10.21203/rs.3.rs-921850/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Transplantation in Newly Diagnosed Type-1 Diabetes Patients: A Phase I/II Randomized Placebo Controlled Clinical Trial

Abstract: BackgroundType-1 diabetes (T1D) occurs following autoimmune-induced pancreatic beta cells death. Among several treatment modalities, Mesenchymal Stem Cells (MSCs) transplantation is promising for autoimmune disorders due to immunomodulation, regeneration, and migration to damaged tissue upon systemic injection. This study assessed the safety and efficacy of intravenous injection of autologous bone marrow-derived MSCs in newly diagnosed T1D patients. MethodsAfter receiving informed consent, 21 patients who met … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…232 The majority of trials have used adult mesenchymal stem cells derived from different origins, hematopoietic stem cells, or a combination of both. 227,233,234 Other trials have demonstrated the potential for the use of human embryonic stem cells and induced pluripotent stem cells to form functionally mature insulin-producing β cells. 227,235,236 The long-term safety of encapsulation devices and long-term viability of transplanted cells are persistent challenges to the widespread use of stem cell-based therapies.…”
Section: Prevention Of Hypoglycemiamentioning
confidence: 99%
See 1 more Smart Citation
“…232 The majority of trials have used adult mesenchymal stem cells derived from different origins, hematopoietic stem cells, or a combination of both. 227,233,234 Other trials have demonstrated the potential for the use of human embryonic stem cells and induced pluripotent stem cells to form functionally mature insulin-producing β cells. 227,235,236 The long-term safety of encapsulation devices and long-term viability of transplanted cells are persistent challenges to the widespread use of stem cell-based therapies.…”
Section: Prevention Of Hypoglycemiamentioning
confidence: 99%
“…It also overcomes the obstacle of limited donor availability 232 . The majority of trials have used adult mesenchymal stem cells derived from different origins, hematopoietic stem cells, or a combination of both 227,233,234 . Other trials have demonstrated the potential for the use of human embryonic stem cells and induced pluripotent stem cells to form functionally mature insulin‐producing β cells 227,235,236 .…”
Section: Introductionmentioning
confidence: 99%